(untitled) (Fiep Bulletin - online, 2012)
The sustainability of a professional is directly connected to the capacity of noticing the possibilities for this professional. The professional graduation in Physical Education is currently, despite of being more focused on the health field, connected to the aesthetic questions. As a consequence it is aimed at and concerned about building a body following standards taken as the aesthetically beautiful. In this study it is proposed a change in the current paradigms of the undergraduate courses in Physical Education for one in which can be viewed the whole of the human being, what happens with human motricity. As a consequence it is proposed the professional graduation in a systemic format, once that, by developing professional activities in Physical Education, this is done with the human being in his integrity and not only from the neck below, as it is currently observed.